(3fSGA UZjQGJs - (3CdchJ, dhjRG eGj,s 1832-1888; (3YjSi, LgjfIs ((3HjQhJ (B:s (3OGQ hecJHI GdgdGd ddfTQ hGdJhRjY,s, 2004)
(3bUU COHjI(B.s
(3fSGA UZjQGJ LRA ef SdSdI QhGFjI eHSWI KfGFjI GddZI (B: (3EfLdjRj(B-(3YQHj(B.s
(3GdfU HGddZJjf GdYQHjI hGdEfLdjRjI(B.s
Keywords: (3GdbUU GdEfLdjRjIs -- (3GdhdGjGJ GdeJMOI GdCeQjcjIs -- (3bQf (B19s